2017
DOI: 10.1111/jvh.12800
|View full text |Cite
|
Sign up to set email alerts
|

Sustained virological response to ombitasvir/paritaprevir/ritonavir and dasabuvir treatment for hepatitis C: Real‐world data from a large healthcare provider

Abstract: Treatment with ombitasvir/paritaprevir/ritonavir and dasabuvir, with or without ribavirin (OPrD ± RBV), was the first interferon-free direct-acting antiviral for hepatitis C virus (HCV) introduced to Israel's national basket of health services in February 2015. Patients with HCV genotype 1 (GT1) and advanced fibrosis (F3-F4) were eligible for treatment in 2015. This study aimed to characterize patients initiating OPrD ± RBV and assess sustained virological response (SVR). A retrospective cohort study was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…Importantly, the potential of “missing” virological failure in those LTFU does have onward implications for persistent transmission and eventual eradication of HCV. Amongst the current real‐world literature, missing SVR data ranges between 2 and 9% in larger observational studies . Elsharkawy et al (2001) report the highest level of loss to follow‐up at 29% in a large observational study of 20 324 genotype 4 patients completing DAA therapy in Egypt .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the potential of “missing” virological failure in those LTFU does have onward implications for persistent transmission and eventual eradication of HCV. Amongst the current real‐world literature, missing SVR data ranges between 2 and 9% in larger observational studies . Elsharkawy et al (2001) report the highest level of loss to follow‐up at 29% in a large observational study of 20 324 genotype 4 patients completing DAA therapy in Egypt .…”
Section: Discussionmentioning
confidence: 99%
“…The ombitasvir/paritaprevir/ritonavir plus dasabuvir combination regimen has been evaluated in many large‐scale real‐world studies and reported consistently high SVR rates with 12‐24 weeks of treatment. In a real‐world study of genotype 1‐infected patients with advanced fibrosis (F3‐F4), the overall SVR rate was 98% (395/403) with this combination . Furthermore, an SVR rate of 97% (170/176) was reported in a subset of more difficult patients (genotype 1b with cirrhosis) .…”
Section: Efficacy In the Real‐world Settingmentioning
confidence: 91%
“…In a real-world study of genotype 1-infected patients with advanced fibrosis (F3-F4), the overall SVR rate was 98% (395/403) with this combination. 13 Furthermore, an SVR rate of 97% (170/176) was reported in a subset of more difficult patients (genotype 1b with cirrhosis). 13 Real-world data from Germany, Spain and Israel have also reported high SVR rates of 96% (n = 892), 96.8% (n = 1567) and 98.8% (n = 416), respectively in patients with genotype-1 infection receiving this regimen.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, 71 million people are chronically infected with the hepatitis C virus (HCV) [1]. Direct-acting antivirals (DAA) provided high sustained virological response (SVR) rates in reallife cohorts [2][3][4], without major safety signals [5][6][7][8][9][10][11][12][13]. Most of these studies have excluded patients with chronic kidney disease (CKD) as Sofosbuvir (SOF) is not recommended in patients with an estimated glomerular filtration rate (eGFR) <30 ml/min/1.73 m 2 [14,15].…”
Section: Introductionmentioning
confidence: 99%